2015
DOI: 10.1021/acsmedchemlett.5b00193
|View full text |Cite
|
Sign up to set email alerts
|

Oxopyrido[2,3-d]pyrimidines as Covalent L858R/T790M Mutant Selective Epidermal Growth Factor Receptor (EGFR) Inhibitors

Abstract: In nonsmall cell lung cancer (NSCLC), the threonine(790)-methionine(790) (T790M) point mutation of EGFR kinase is one of the leading causes of acquired resistance to the first generation tyrosine kinase inhibitors (TKIs), such as gefitinib and erlotinib. Herein, we describe the optimization of a series of 7-oxopyrido[2,3-d]pyrimidinyl-derived irreversible inhibitors of EGFR kinase. This led to the discovery of compound 24 which potently inhibits gefitinib-resistant EGFR(L858R,T790M) with 100-fold selectivity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Taiho Pharma is known to be developing TAS-121 as an oral mutant EGFR selective inhibitor and is currently in Phase 1 clinical trials, but no structure has yet been disclosed. In addition, numerous additional pre-clinical T790M inhibitors have been described in the literature (For example, see: [59][60][61]).…”
Section: Resistance Mutationsmentioning
confidence: 99%
“…Taiho Pharma is known to be developing TAS-121 as an oral mutant EGFR selective inhibitor and is currently in Phase 1 clinical trials, but no structure has yet been disclosed. In addition, numerous additional pre-clinical T790M inhibitors have been described in the literature (For example, see: [59][60][61]).…”
Section: Resistance Mutationsmentioning
confidence: 99%
“…The inhibition activity of pyrido [2,3-d]pyrimidine derivatives toward CK2 kinase has not been studied. Noteworthy, the substituted pyrido [2,3-d]pyrimidines are the inhibitors of EGFR [21][22][23][24], Cyclin-Dependent kinases [25,26], Src-tyrosine kinase [27,28] and c-Jun N-Terminal kinase (JNK) [29,30]. It was found that among 2-substituted pyrido [2,3-d]pyrimidin-7-one derivatives there are powerful selective inhibitors of CDK4/6 kinase (Palbociclib) [25], Abl kinase (PD173955) [31,32] and p38 MAP kinase (Pamapimod) [33] which are effective in the treatment of autoimmune and cancer diseases.…”
Section: Bioorganic Chemistrymentioning
confidence: 99%
“…Resistance to such drugs is most commonly a result of mutations in the EGFR catalytic domain, with the threonine 790 to methionine 790 mutation (T790M) present in approximately half of the NSCLC patients who develop drug resistance. Research in our department and others has focused on exploiting this mutation through the development EGFR T790M -targeted therapies. Through these efforts, scientists in our medicinal chemistry group identified 1 as a preclinical candidate. , …”
mentioning
confidence: 99%
“…Through these efforts, scientists in our medicinal chemistry group identified 1 as a preclinical candidate. 14,15 The discovery route to prepare 1 implemented an S N Ar reaction between substitued aniline derivative 2 and chloropyrimidine 3 in superheated (100 °C) methanol using a stoichiometric amount of acetic acid as a promoter (Scheme 1). 16 While this method enabled the delivery of material to support early toxicology studies, observations made during these campaigns indicated that scale-up of this process would be challenging.…”
mentioning
confidence: 99%